2020
DOI: 10.3390/w12102869
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection and Attribution of Groundwater Level Variations in the Amu Darya Delta

Abstract: In the past few decades, the shrinkage of the Aral Sea is one of the biggest ecological catastrophes caused by human activity. To quantify the joint impact of both human activities and climate change on groundwater, the spatiotemporal groundwater dynamic characteristics in the Amu Darya Delta of the Aral Sea from 1999 to 2017 were analyzed, using the groundwater level, climate conditions, remote sensing data, and irrigation information. Statistics analysis was adopted to analyze the trend of groundwater variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The expansion of arable land and the increase in output value result in an increase in water consumption (Li et al, 2019). Similar to this paper, many studies on irrigation areas in arid areas have shown the large impact of human activities on groundwater in irrigation areas (Li et al, 2020;Pan et al, 2020). In our attribution analysis, with the rise of the groundwater level, it is particularly worth noting that as a cause of rising groundwater, the change in the flow of the Amudarya River was not closely related to groundwater.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The expansion of arable land and the increase in output value result in an increase in water consumption (Li et al, 2019). Similar to this paper, many studies on irrigation areas in arid areas have shown the large impact of human activities on groundwater in irrigation areas (Li et al, 2020;Pan et al, 2020). In our attribution analysis, with the rise of the groundwater level, it is particularly worth noting that as a cause of rising groundwater, the change in the flow of the Amudarya River was not closely related to groundwater.…”
Section: Discussionsupporting
confidence: 73%
“…Only one study has described the macroscopic changes in the region (Pan et al, 2020), and there is a lack of groundwater research on the characteristics of the irrigation area.…”
Section: Introductionmentioning
confidence: 99%
“…The TWS can be divided into three parts, including the inflow from the Amu Darya River, the precipitation, and the groundwater. However, the data of groundwater are not yet available and were calculated in the balance of supply-demand as the residual item [ 9 , 18 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It used to be the world's fourth-largest lake but has shrunk over the past few decades [48]. The water supply for the Aral Sea is dependent on the Amu Darya and Syr Darya Rivers, which are the two major tributaries of the Aral Sea Basin [37,[49][50][51]. These two rivers originate from the Pamirs and Tian Shan Mountains and run through the territory of Central Asia and Afghanistan [52,53].…”
Section: Study Area and Vegetation Inventory Datamentioning
confidence: 99%